Additive manufacturing of bioactive glass in a biodegradable matrix - Pires, Liliana S. O. (2022)
Bioactive glass can induce a specific and fast response in the human body that supports tissue regeneration. It is possible to control the design of customized bioapplications with advanced technologies. Although currently used in research, only a few of these technologies have been approved by the FDA to be applied in Tissue Engineering. There is dedicated additive manufacturing equipment to manufacture biomaterials. Since they are emerging technologies in emerging fields of application it is necessary to study and develop formulations with suitable processing characteristics [1]. Formulations of bioactive glass (CaO·P2O5·MgO·SiO2 system) in two different biodegradable matrices (polylactide (PLA) and polycaprolactone (PCL)) were prepared and processed by material extrusion process, namely by Fused Filament Fabrication technique.. The polymer (PLA or PCL) involves bioactive particles in biocompatible media and allows to acquire extrudable skills. The formulations with different solid contents (20–50 wt.%) were prepared using a brabender mixer type and were characterized by different techniques (e.g., X-ray diffraction (XRD), differential scanning calorimetry (DSC), melt flow index (MFI)). The inorganic particles influence the rheological and thermal properties of bioactive glass composites. The viscosity decreases with the increase of bioactive glass content in the polymer matrix. Mechanical standard samples and scaffolds were printed and characterized. Bioactive glass composites until 40 wt.% of solid content can be printed. The bioactive glass improves the mechanical resistance of composites compared to a neat polymer matrix. However, formulations with high bioactive glass solid content (50 wt.%) showed printing limitations by their brittleness and clogging tendency.